Fabrication of covered porous PLGA microspheres using hydrogen peroxide for controlled drug delivery and regenerative medicine - Bae, Soon Eon; Son, Jun Sik; Park, Kwideok; Han, Dong Keun (ELSEVIER SCIENCE BV, 2009)
Poly(lactic-co-glycolic acid) (PLGA) microsphere has been a useful tool in delivering therapeutic drugs and biologically active proteins. In this study, a covered porous PLGA microsphere was manufactured using W-1/O/W-2 double emulsion solvent evaporation method, utilizing hydrogen peroxide as a novel porogen. An enzymatic reaction between hydrogen peroxide and catalase produced oxygen bubbles and thus many internal pores within microsphere were naturally developed. When different molar ratios between lactide and glycolide in PLGA were examined, the ratio, 50:50 showed the most organized porous microstructure. Higher molecular weight of PLGA seemed to be favorable in creating a porous structure. By testing various concentrations of hydrogen peroxide, it was found that rather concentrated one was more efficient in developing a porous network in the microspheres. The source of the skin layer that covers the whole surface of the microsphere was found to be PLGA, not polyvinyl alcohol (PVA). The residual amount of hydrogen peroxide was negligible after a thorough evaporation of PLGA microsphere. When release profiles of dexamethasone (Dex) with morphologically different microspheres such as, nonporous, covered porous, and porous, were investigated for up to 28 days in vitro, their release patterns were found to be significantly different on a temporal basis. The present work demonstrated that the covered porous PLGA microspheres could be successfully fabricated using hydrogen peroxide and that the covered skin layer on the PLGA microsphere played an important role in determining the characteristic release profiles of Dex. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: BIODEGRADABLE POLYMERIC MICROSPHERES; SOLVENT EXTRACTION/EVAPORATION METHOD; IN-VITRO RELEASE; GROWTH-FACTOR; GELATIN MICROSPHERES; PHASE-SEPARATION; PROTEIN; DEXAMETHASONE; MORPHOLOGY; PROFILES